FRICTION STIR SPOT WELDING OF DISSIMILAR ALUMINIUM ALLOYS - (:unkn) unknown (PUBL HOUSE BULGARIAN ACAD SCI, 2016)
Friction stir spot welding (FSSW) has been proposed as an effective technology to spot weld the so-called difficult to be welded metal alloys such as thin sheets aluminum alloys and dissimilar materials. FSSW is derived from friction stir welding technology, its principle benefit being low cost joining, lower welding temperature and shorter welding time than conventional welding methods. In this study, dissimilar AlMg3 and AlCu4Mg1 aluminium alloy plates were FSSWed by offsetting the low strength sheet on upper side of the weld. The effects of tool rotation speed on the microstructure, lap shear fracture load (LSFL), microhardness and fracture features of the weld are investigated by constant welding parameters. The maximum LSFL was obtained by increasing the tool rotational speed. However, the joints exhibited pull-out nugget fracture mode under lap shear tensile testing conditions. The largest completely bonded zone was observed as 5.86 mm which was narrower at the opposite position of the joint.
Keywords: friction stir spot welding; aluminium alloys; mechanical properties; dissimilar joint; welding parameters; PIN LENGTH; JOINTS; PARAMETERS; FAILURE; MICROSTRUCTURE; STRENGTH; SHEETS; FSSW